An Exploratory Study on the Structural and Demographic Predictors of Hate Crime Across the Rural-Urban Divide - Holder, Eaven (Victims & offenders, 2024)
Scholarly attention directed toward hate crime, especially across communities, has grown in the past two decades. Rural communities, however, have been neglected in such empirical inquiry, driving issues on the ability to draw reliable conclusions on ecological variations of such offenses. Thus, we examined structural and demographic predictors of hate crime across rural and urban counties, focusing our attention on whether patterns varied in predicting anti-Black, Hispanic, and White crimes from 2012 through 2016. Using social disorganization and the defended communities perspective as explanatory frameworks, we find important differences and similarities between these settings, with implications for theory and research.